Turning a Blind Eye and Unformulated Knowledge in the Family - Keini, Noga; Zerem-Ulman, Vardit (Advances in Social Sciences Research Journal, 2022)
This article addresses the issue of blindness, or turning a blind eye, employing two alternative realms: Psychoanalysis, and System and Family Therapy. Reference is made to deliberately turning a blind eye to well-established facts as part of a mental mechanism in individuals for whom dealing with reality is unbearably difficult. A disregard for facts may be viewed as an instrument that eventually leads to a distortion of reality and to deficient, unconsolidated self-esteem, with shades at times of psychosis. The subject is approached from two opposing realms, to underscore the importance of psychoanalysis as well as that of system and family therapy in the present context [11]. Two clinical cases are illustrated.